Growth and mortality parameters of P. senegalensis and P. typus (Sciaenidae) in nearshore waters of Benin (West Africa) and their implications for management and conservation - Sossoukpe, E.; Nunoo, F.K.E.; Ofori-Danson, P.K.; Fiogbe, E.D.; Dankwa, H.R. (Fisheries Research, 2013)
Most fisheries in Africa are overexploited or are at the peak of exploitation. A key contributor to this overfishing is poor data on fisheries, inefficient management strategies and unenforced policies. Pseudotolithus species off Benin nearshore waters are mainly fished by beach seining. Unfortunately, since 1994, the production of these species has been decreasing, with more small-sized fishes appearing in catches, and little is known about the species' population dynamics. Therefore, the growth and mortality parameters of two commercially important Sciaenids (Pseudotolithus senegalensis and Pseudotolithus typus) off Benin's nearshore waters were investigated using length-frequency data of 2019 specimens sampled from beach seine hauls over a period of 18 months. The length-weight relationship was computed from linear regression analysis. P. senegalensis exhibited isometric growth while P. typus exhibited negative allometric growth. The von Bertalanffy growth constants for P. senegalensis were TL∞=51.4cm, K=0.24yr-1, and t0=-0.60yr with a derived growth performance index of φ'=2.753. The corresponding estimates for P. typus were TL∞=56.2cm, K=0.19yr-1, t0=-0.73yr and φ'=2.652. The growth patterns determined by the growth performance index (φ') were higher for P. senegalensis than for P. typus of similar sizes. The total mortality rate, Z, for P. senegalensis was estimated as 4.39yr-1, with the fishing mortality, F, being calculated as 3.70yr-1. The mortality estimates for P. typus were Z=4.12yr-1 and F=3.70yr-1. The exploitation rate of the two fish species was higher than the optimum exploitation criterion, which is indicative of over-fishing. Several immediate management actions, such as size-limit regulation by gradually increasing beach seine mesh size and time-limit regulation by restricting fishing outside the spawning season, are considered necessary for sustainable exploitation of these stocks. © 2012.
Keywords: Benin nearshore waters; Fisheries management; Growth; Mortality; Pseudotolithus